Tumors that mimic asbestos-related mesothelioma: time to consider a genetics-based tumor registry? - Kerger, Brent D.; James, Robert C.; Galbraith, David A. (Frontiers in Genetics, 2014)
The diagnosis of mesothelioma is not always straightforward, despite known immunohistochemical markers and other diagnostic techniques. One reason for the difficulty is that extrapleural tumors resembling mesothelioma may have several possible etiologies, especially in cases with no meaningful history of amphibole asbestos exposure. When the diagnosis of mesothelioma is based on histologic features alone, primary mesotheliomas may resemble various primary or metastatic cancers that have directly invaded the serosal membranes. Some of these metastatic malignancies, particularly carcinomas and sarcomas of the pleura, pericardium and peritoneum, may undergo desmoplastic reaction in the pleura, thereby mimicking mesothelioma, rather than the primary tumor. Encasement of the lung by direct spread or metastasis, termed pseudomesotheliomatous spread, occurs with several other primary cancer types, including certain late-stage tumors from genetic cancer syndromes exhibiting chromosomal instability. Although immunohistochemical staining patterns differentiate most carcinomas, lymphomas, and mestastatic sarcomas from mesotheliomas, specific genetic markers in tumor or somatic tissues have been recently identified that may also distinguish these tumor types from asbestos-related mesothelioma. A registry for genetic screening of mesothelioma cases would help lead to improvements in diagnostic criteria, prognostic accuracy and treatment efficacy, as well as improved estimates of primary mesothelioma incidence and of background rates of cancers unrelated to asbestos that might be otherwise mistaken for mesothelioma. This information would also help better define the dose-response relationships for mesothelioma and asbestos exposure, as well as other risk factors for mesothelioma and other mesenchymal or advanced metastatic tumors that may be indistinguishable by histology and staining characteristics.